GAMBARAN PENDIDIKAN PESANTREN PADA NOVEL NEGERI 5 MENARA KARYA A. FUADI: PENDEKATAN MIMETIK - Winarti Winarti S.Pd., M.Pd (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aimed to describe the picture of pesantren education in Negeri 5 Menara novel works of A. Fuadi, describing patterns of pesantren education in Negeri 5 Menara novel work of A. Fuadi mimetic approach, and knowing the differences and similarities between the pattern of the existing education at boarding school novel with real life. The research was carried out in Ar-Raudhatul boarding Hasanah located at Jalan Jamin Ginting Km. 11 Medan Tuntungan. The study began in December 2012 until February 2013. Sources of data in this study is novel Negeri 5 Menara works of A. Fuadi as primary data. Literature books, books that are relevant to the study of research assessment, and boarding Ar-Raudhatul Hasanah as secondary data in this study. Research data collection techniques are technical documentation, observation (observation), and interviews. Researchers analyzed the content (content analysis). Design research by reading the material carefully studied the novel Negeri 5 Menara, collecting research data related to the study of the novel, composing, mengklarifikasikannya, analyze, and interpret.The results of this study indicate that the picture of education in schools is the education system to adopt a 24-hour full-oriented religion. What was presented by A. Fuadi is a picture of an education based on the reality of the life that he copied and there are some parts that he kreasikan with creative imagination. While the pattern of pesantren education itself is a pattern of modern education, are not left with the other public schools. Pesantren managed to